Evaluation and Modelling of Water Absorption Characteristics of Paddy - Kale, S. J.; Jha, S. K.; Jha, G. K.; Samuel, D. V. K. (Journal of Agricultural Engineering, 2014)
Water absorption characteristics of paddy (PB1121) were evaluated over a temperature range 40 to 80oC. The equilibrium moisture content of the grain during water absorption varied from 48.24 to 55% (d.b.). Average critical moisture content of PB1121 for soaking during parboiling was 41.67% (d.b.). Average moisture diffusivity during water absorption process was 5.06x10-10 m2.s-1 and activation energy was 53.85 kJ.mol-1. Modelling of water absorption behaviour using Page model revealed that it fitted well at individual temperatures (R2>0.9). However, the Generalized Page model provided poor performance with R2 of 0.65, MSE 0.0018 and mean relative deviation modulus (% P) 48.02, whereas multi-layer perceptron neural network model fitted well with R2 =0.99, MSE =0.0013 and P =14.69%.